First-principles analysis of the electric structure, optical properties, and phonon transmission of a VTe monolayer in the rock-salt phase - Mustafa M. Jaafar; Jabbar M. Khalaf Al-zyadi (Genius Journals, 2023)
First-principles simulations based on density functional theory (DFT) are used to examine the structural, electric, and optical properties of the (RS) VTe monolayer as well as the phonon transport. The (RS) VTe monolayer demonstrated distinct electric characteristics along with a wide absorption spectrum spanning the visible to ultraviolet range. Additionally, a decrease in its convergent phonon scattering rate was discovered. These results demonstrate the possibility for more theoretical and experimental studies of the electric, structure, optical properties, and thermal conductivity of the VTe monolayer. The results of the experiments have demonstrated that the monolayer of (RS) VTe has the property of being a half-metal. When the energy levels crossed the Fermi level in the spin-up position, the substance displayed metallic characteristics. In contrast, in the spin-down configuration, an energy gap appeared on both sides of the Fermi level, resulting in the creation of a semiconductor. This is shown by the presence of a gap between the conduction and valence bands, with the total energy gap of the compound determined by the sum of both gaps. The energy gap of the (RS) VTe monolayer was measured to be 0.7 eV, which is half the size of the energy gap of a typical metal (0.4 eV). Furthermore, the half-metal character of the (RS) VTe monolayer resulted in a magnetic moment per unit cell similar to 3µB revealing a significant polarization at the Fermi level.
Keywords: VBi; Half-metallic ferromagnetism; monolayer properties